Barriers to implementation of the HIV guidelines in the IMCI algorithm among IMCI trained health workers in Zambia - Kalesha Penny; Mutale Wilbroad; Mugala Nantalile; Sinyinza Elijah (BMC, 2010)
Abstract Background Zambia adopted integrated management of Childhood illnesses (IMCI) in 1995 and a number of adaptations have been made to the generic WHO/UNICEF IMCI guidelines to better conform to Zambia's health service needs. One significant adaptation is the incorporation of HIV guidelines into the IMCI algorithm. Since 2004, health workers that have undergone IMCI case management training have also received training in HIV assessment. During initial follow-up visits in 11 districts 90 health workers were assessed in 2007 to determine their adherence to the IMCI algorithm. The assessment showed that 97% of the health workers assessed did not review or mention the HIV guidelines even though they had received HIV training as part of IMCI. This study aimed to explore reasons for non-adherence to HIV guidelines in the IMCI algorithm and make recommendations on how this can be improved. Methods Both quantitative and qualitative methods were used to collect information from eligible health workers. Forty (40) health workers were randomly selected from among those who received initial follow-up visits between March 2007 and January 2008. The health workers were selected from eight districts in four provinces of Zambia. Qualitative data was collected using Focus group discussion and key informant interviews Results 83% of the respondents said they had no difficulties in following the HIV adapted IMCI guidelines. 17% said they had difficulties. Of those who admitted having difficulties (60%) had difficulties in HIV assessment. Interesting, prompting and focus group discussions revealed that most respondents actually had difficulties in HIV assessment but could not admit it readily. Some barriers that contributed to non-adherence to the guidelines included lack of time due to inadequate staffing, lack of privacy in the health facilities and HIV related stigma from both caregivers and health workers. Frequent use of guidelines and supervision appeared to re-enforce adherence to the guidelines. Conclusion The findings in this study suggest that training in HIV adapted IMCI guidelines is not sufficient to enable health workers to actually use their knowledge in their daily practice. Barriers may exist which prevent them from adhering to the guidelines. Addressing these barriers is critical in increasing the uptake of paediatric ART in Zambia